2010
DOI: 10.1016/j.bbrc.2010.04.155
|View full text |Cite
|
Sign up to set email alerts
|

Purification, characterization and substrate specificity of a trypsin from the Amazonian fish tambaqui (Colossoma macropomum)

Abstract: An enzyme was purified from the pyloric caecum of tambaqui (Colossoma macropomum) through heat treatment, ammonium sulfate fractionation, Sephadex G-75 and p-aminobenzamidine-agarose affinity chromatography. The enzyme had a molecular mass of 23.9 kDa, NH(2)-terminal amino acid sequence of IVGGYECKAHSQPHVSLNI and substrate specificity for arginine at P1, efficiently hydrolizing substrates with leucine and lysine at P2 and serine and arginine at P1'. Using the substrate z-FR-MCA, the enzyme exhibited greatest a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…Similar results were obtained from trypsin activity extracted from the viscera of Monterey sardine Kishimura et al (2006) or true sardine (Yanez et al, 2005) and alkaline proteases extracted from digestive system of carp (Catla catla) (Khangembam et al, 2012). In this reported, (Marcuschi et al, 2010) pointed out that trypsin extracted from the digestive system of fish is normally active in the alkaline region (from pH 7-12) using BAPNA as a model of substrate.…”
Section: Determination Of Optimum Phsupporting
confidence: 73%
“…Similar results were obtained from trypsin activity extracted from the viscera of Monterey sardine Kishimura et al (2006) or true sardine (Yanez et al, 2005) and alkaline proteases extracted from digestive system of carp (Catla catla) (Khangembam et al, 2012). In this reported, (Marcuschi et al, 2010) pointed out that trypsin extracted from the digestive system of fish is normally active in the alkaline region (from pH 7-12) using BAPNA as a model of substrate.…”
Section: Determination Of Optimum Phsupporting
confidence: 73%
“…Fish trypsins have molecular masses between 23 and 28 kDa, e.g., Oreochromis niloticus (23.5 kDa) [1], Colossoma macropomum (23.9 kDa) [5], Gadus macrocephalus (24 kDa) [19], Pseudupeneus maculatus (24.5 kDa) [6], Sardina pilchardus (25 kDa) [10], Diapterus rhombeus (26.5 kDa) [3], Salaria basilisca (27 kDa) [20], Pterygoplichthys disjunctivus (27.5 kDa) [21], Arapaima gigas (28 kDa) [2], Pomatomus saltatrix (28 kDa) [22], and Lutjanus synagris (28.4 kDa) [4]. …”
Section: Resultsmentioning
confidence: 99%
“…Marcuschi et al (2010) reported the purification of trypsin from the pyloric caecum of tambaqui (C. macropomum) through heat treatment, ammonium sulfate fractionation, Sephadex-G-75 and p-aminobenzamidineeagarose affinity chromatography with a purification yield of 30.0%. In the same context, Silva et al (2011) purified a trypsin from the viscera of the silver mojarra (Diapterus rhombeus) in a three step process: heat treatment, ammonium sulphate fractionation and molecular exclusion chromatography (Sephadex-G-75), with final specific activity 86-fold higher than that of the enzyme extract and yield of 22.1%.…”
Section: Recovery and Purification Of Trypsins From Fish Wastementioning
confidence: 99%